2014
DOI: 10.1186/1752-0509-8-55
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β stimulation in human and murine cells reveals commonly affected biological processes and pathways at transcription level

Abstract: BackgroundThe TGF-β signaling pathway is a fundamental pathway in the living cell, which plays a key role in many central cellular processes. The complex and sometimes contradicting mechanisms by which TGF-β yields phenotypic effects are not yet completely understood. In this study we investigated and compared the transcriptional response profile of TGF-β1 stimulation in different cell types. For this purpose, extensive experiments are performed and time-course microarray data are generated in human and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 62 publications
(72 reference statements)
1
19
0
1
Order By: Relevance
“…Moreover, PDGF could induce endothelial differentiation of MSCs [ 99 ], whereas TGF- β plays an important role in cell differentiation and vascular remodeling [ 100 ]. It has been revealed that TGF- β could increase the expression of smooth muscle β -actin while decreasing the expression of gelsolin according to proteomic profiling analysis [ 101 ], which will lead to more focused and in-depth research on the influences of TGF- β on endothelial differentiation of MSCs.…”
Section: Endothelial Differentiation Of Mscsmentioning
confidence: 99%
“…Moreover, PDGF could induce endothelial differentiation of MSCs [ 99 ], whereas TGF- β plays an important role in cell differentiation and vascular remodeling [ 100 ]. It has been revealed that TGF- β could increase the expression of smooth muscle β -actin while decreasing the expression of gelsolin according to proteomic profiling analysis [ 101 ], which will lead to more focused and in-depth research on the influences of TGF- β on endothelial differentiation of MSCs.…”
Section: Endothelial Differentiation Of Mscsmentioning
confidence: 99%
“…Anti-inflammatory cytokines including TGF-β1 and IL-10 have come under increasing scrutiny for their association with severe TB ( 18 , 21 , 27 29 ). TGF-β1 is highly conserved across taxa ( 30 ) and can influence many cell types ( 31 34 ) by signaling through the TGFβR1/TGFβR2 receptor complex ( 35 ). TGF-β1 has a variety of inhibitory effects including the ability to downregulate macrophage activation and effector function ( 36 40 ), decreasing cytokine secretion by macrophages and cytotoxic T cells ( 41 , 42 ), and decreasing proliferation of T cells ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…The topographic representation of E/M states derived above can be used to visualize and interpret RNA-sequencing (RNA-seq) data obtained while the cells are undergoing phenotypic transformations. We first consider the classical example of TGF-β-induced EMT in a human lung adenocarcinoma cell line(42).Fig. 4Areports the trajectory of the states obtained from the bulk RNA-seq data recorded at different time points after TGF-β induction.…”
mentioning
confidence: 99%